The discourse potential of underspecified structures - Steube, Anita (Language, Context and Cognition, 2008)
The volume demonstrates the interdependence of man's language capacity and his other conceptual capacities. This enables linguistic structures to be minimalised, and for extra-linguistic domains to provide much of the interpretations of sound and meaning. Underspecification is demonstrated in the word formation of Indo-European, Late Archaic Chinese and modern Khmer; on the word- and sentence levels by the event structures of German; and in the information structure predominantly of languages with the so-called free word order: German, Slavic languages, Arabic compared with English and the ton